Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Scalable optical fiber reactor for photocatalytic H2 production: addressing scattering issues - Walko, Priyanka S.; Devi, R. Nandini (International Journal of Hydrogen Energy, 2023)
Scattering is one of the main challenges in scaling up photocatalytic water splitting using the most prevalent powder catalysts. This can be overcome by decoupling the reaction medium from light transmission, as in the case of optical fibers. Here we explore utilizing optical fibers coated with 5 wt% CuO supported on TiO2 for photocatlytic H2 production from water-methanol mixtures. CuO/TiO2 is a well studied photo catalyst in which photoreduced Cu species are known to act as sensitizers for inducing visible light activity. Lower activity of sequentially coated systems indicates that appropriate interfaces of active Cu and TiO2 with water are desirable. The scalability of such optical fiber-based systems along with potential in non-potable turbid water media are demonstrated. Maximum activity of 22 mmoles of H2 in 8 h was obtained with 50 mg of catalyst coated on optical fibers, which increases linearly with increase in fiber numbers, whereas, drastic reduction in activity is observed in powder catalyst upon increasing the catalyst quantity. A one-to-one comparison of 700 mg of catalyst in powder form and coated on optical fibers indicates more than one order enhancement in activity in the optical fiber based system. In addition, -70% retention in activity in highly turbid non-potable water was observed as compared to powdered system which shows complete reduction in the activity by 99.99%. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CuO; Optical fibers; photocatalytic water splitting; TiO2; Total internal reflection; Visible light utilisation

Hydrogen evolution via photocatalytic reforming of biomass with palladium nanoparticles decorated g-C3N4 nanosheets - Thara, Chinnu R.; Walko, Priyanka S.; Mathew, Beena (Renewable Energy, 2024)
Fossil fuel depletion and environmental toxins have made photocatalytic H2 production of paramount significance. A novel and unique technique for producing sustainable H2 and valorizing biomass using infinite solar energy is biomass photoreformation. Nevertheless, this environmentally friendly method is usually linked to severe reaction circumstances, insufficient selectivity, and restricted biomass conversion. Here, we present a novel one-pot photoreformation technique over porous g-C3N4 nanosheets surface-modified with Pd nano- particles to convert D-glucose to H2. By stacking the g-C3N4 photocatalyst into a 2D nanosheet structure, some of its inherent drawbacks can be mitigated. Furthermore, the inclusion of noble metal nanoparticles in these g-C3N4 nanosheet structures could significantly boost existing photocatalytic activity. The majority of solar radiation is composed of visible light, which makes up 45% of it, and ultraviolet light, which makes up 5%. Therefore, our focus has been on utilizing abundant visible light to facilitate biomass reformation. After 4 h of continuous irradiation, our composite photocatalyst exhibited exceptional visible light activity; its H2 evolution was 1839.84 mu molg- 1h- 1 , or about 27 times higher than that of undoped g-C3N4 nanosheets. The effectiveness of three different Pd loadings on g-C3N4 nanosheets for glucose reforming was examined. In the quest for an improved H2 evolution visible light active photocatalyst, g-C3N4 nanosheets made at various pyrolysis temperatures loaded with optimized Pd weight percentage were also examined.
Keywords: Biomass; D -glucose; g-C 3 N 4 nanosheets; Hydrogen evolution; palladium nanoparticles; Photocatalytic reforming